Assessment and analysis of riparian zone downstream of Brantas River at three different points in Mojokerto region, East Java, Indonesia - Khalifa Abdalnasser A M; Leksono Amin Setyo; Marjono; Rachmansyah Arief (BIO Web of Conferences)
This study aims to analyse the species richness downstream of the Brantas River riparian zone in the Mojokerto Region. The research was conducted in December 2023. The method used in this study was to analyse the vegetation ecology in which the quadrat technique was applied to a 5 x 5 m plot size to collect primary data on the riparian plants. The parameters of plant composition were analysed by measuring their relative abundance (RA), relative frequency (RF) and importance value index (IVI). This study discovers a total of 50 species (Herbs 42, tree 3, liana 3 and shrubs 2). The results showed that site 1 had 8659 individuals, with 20 species belonging to 13 families. In site 2, 2872 individuals were found with 22 species in 14 families and 2361 individuals with 33 species belonging to 22 families. The plant species with high IVI was Lemna perpusilla Torr, covering 61.49% in site 1, 43.40% in site 2 and 41.97% in site 3.